Using patient experience in optimizing the total knee arthroplasty patient journey - Nienke Wolterbeek; Dieuwertje Hiemstra; Fiona van der Hoeven; Kiem Auw Yang (The Beryl Institute, 2019)
Information was used to improve the patient journey and to achieve patient-centered care. Patients (>18 years, purposive sampling) were interviewed once at one point of their total knee arthrosis journey within the hospital setting. Patients were accompanied and observed during their hospital visit by one of the 19 healthcare professionals which were trained as interviewers. A qualitative research approach with in-depth and semi-structured interviews using a standardized interview guide were used to gather an in-depth understanding of the perceptions of patients. Interviews were written out with the emphasis on positive and negative feedback, quotes and observations that were made. The audio recordings were verbatim transcribed and coded using selective and open coding. Thirty-five semi-structured interviews were conducted. Five different themes were identified: overall experience, waiting, communication, information and facilities. Several easy fixes were dealt with immediately to improve service quality, productivity and the organization of the healthcare service. Other improvements were discussed with the stakeholders and were resolved directly or were planned for the long-term. Involving patients and let them collaborate with healthcare professionals is essential in optimizing patient-centered care. Most feedback was related to clarification and comprehensibility of the patient journey, to improve autonomy and to remove uncertainty of the patients. Continuity of care with medical personnel, personal attention and recognition of the problem are fundamental during the knee arthrosis patient journey. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.